(untitled) (Eurasian Medical Research Periodical, 2026)
This research focuses on evaluating changes in leptin and adiponectin concentrations in individuals undergoing bariatric surgery. These adipocytokines, which regulate fat metabolism and contribute to the progression of obesity, are key elements in its pathophysiology. The study enrolled 44 patients treated at the Endocrinology Department of TMA and Medion Family Hospital between 2022 and 2024. Participants were allocated into two cohorts: those who underwent gastric bypass (n = 19) and those who received sleeve gastrectomy (n = 25). Prior to and following the surgical intervention, biochemical indicators, hormonal profiles, and lipid metabolism parameters were analyzed. Twenty-four months post-operation, patients demonstrated a marked reduction in leptin and a notable rise in adiponectin, underscoring the positive metabolic impact of bariatric procedures in individuals with obesity